2019
DOI: 10.1016/j.actamat.2019.07.046
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of precipitates and tensile twins in magnesium alloys

Abstract: Although magnesium alloys deform extensively through shear strains and crystallographic re-orientations associated with the growth of twins, little is known about the strengthening mechanisms associated with this deformation mode. A crystal plasticity based phase field model for twinning is employed in this work to study the strengthening mechanisms resulting from the interaction between twin growth and precipitates. The full-field simulations reveal in great detail the pinning and de-pinning of a twin boundar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…The studies presented here span the scale of individual dislocations (Section ) over single grains (Section ) up to grain aggregates (Section ). Especially for studying the interaction of individual grains, it is a common approach to use experimentally obtained microstructures as input for the simulations .…”
Section: Multiphysics At and Below The Grain Scalementioning
confidence: 99%
See 4 more Smart Citations
“…The studies presented here span the scale of individual dislocations (Section ) over single grains (Section ) up to grain aggregates (Section ). Especially for studying the interaction of individual grains, it is a common approach to use experimentally obtained microstructures as input for the simulations .…”
Section: Multiphysics At and Below The Grain Scalementioning
confidence: 99%
“…This model allows the concurrent description of dislocation plasticity and heterogeneous twinning behavior including twin nucleation, propagation, and growth in Mg alloys and was implemented in DAMASK. In the following, the essential aspects of the model have been compiled from Liu et al and its capabilities are demonstrated with the help of three application examples …”
Section: Multiphysics At and Below The Grain Scalementioning
confidence: 99%
See 3 more Smart Citations